2018
DOI: 10.1371/journal.pntd.0006243
|View full text |Cite
|
Sign up to set email alerts
|

An insight into the salivary gland and fat body transcriptome of Panstrongylus lignarius (Hemiptera: Heteroptera), the main vector of Chagas disease in Peru

Abstract: Triatomines are hematophagous arthropod vectors of Trypanosoma cruzi, the causative agent of Chagas Disease. Panstrongylus lignarius, also known as Panstrongylus herreri, is considered one of the most versatile triatomines because it can parasitize different hosts, it is found in different habitats and countries, it has sylvatic, peridomestic and domestic behavior and it is a very important vector of Chagas disease, especially in Peru. Molecules produced and secreted by salivary glands and fat body are conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 103 publications
(115 reference statements)
0
19
0
1
Order By: Relevance
“…Por su parte, Nevoa, Mendes, da Silva, Soares, Oliveira, Ribeiro (19) en su artículo científico establecieron que los triatominos eran artrópodos hematófagos vectores de Trypanosoma cruzi, el agente causante de la enfermedad de Chagas Además, se ha establecido que Panstrongylus lignarius, considerado uno de los triatominos más versátiles porque podía parasitar a diferentes hospederos, se encontraba en diferentes hábitats y países, tenía un comportamiento selvático, peri doméstico y doméstico, y era un vector muy importante de la transmisión de enfermedad de Chagas, especialmente en el Perú (19) .…”
Section: Discussionunclassified
“…Por su parte, Nevoa, Mendes, da Silva, Soares, Oliveira, Ribeiro (19) en su artículo científico establecieron que los triatominos eran artrópodos hematófagos vectores de Trypanosoma cruzi, el agente causante de la enfermedad de Chagas Además, se ha establecido que Panstrongylus lignarius, considerado uno de los triatominos más versátiles porque podía parasitar a diferentes hospederos, se encontraba en diferentes hábitats y países, tenía un comportamiento selvático, peri doméstico y doméstico, y era un vector muy importante de la transmisión de enfermedad de Chagas, especialmente en el Perú (19) .…”
Section: Discussionunclassified
“…The ratio of translatable transcripts in secreted and housekeeping peptides in R. neglectus SGs and INT (Table 1) was similar to that found in the literature for other triatomines. T. brasiliensis (Santos et al, 2007) had the most secreted proteins in SGs, followed by: R. prolixus (Ribeiro et al, 2004), Panstrongylus lignarius (Nevoa et al, 2018), and Triatoma dimidiata (Kato et al, 2010); with housekeeping following in second in the number of transcripts found in SGs of T. dimidiata and R. prolixus (Ribeiro et al, 2004;Kato et al, 2010). In R. neglectus SGs, a higher number of transcripts of proteins classified as housekeeping were also found than in the other classes analyzed (Santiago et al, 2016).…”
Section: Populations Of Transcripts Translatable Into Secretable and Non-secretable Peptides In R Neglectus Sgs And Intmentioning
confidence: 93%
“…As in other hematophages, several inhibitors are related to the insect feeding process, such as serine protease inhibitor proteins that participate by antagonizing coagulation and the complement system (Nevoa et al, 2018). Still, there is a predominance of several synthesizing enzymes composing the "other classes" group (Figure 8), whose transcripts are also present among those that are part of intrathecidal metabolic pathways (Figure 12A).…”
Section: Feeding Promotes Expression Of Important Molecules To Degrade Food and Compete With Microbiota For Nutrients To Prevent Early Inmentioning
confidence: 98%
See 1 more Smart Citation
“…HTDS can also advance our research related to MUVE. HTDS has allowed us to improve vector monitoring and understanding of vector capacity by providing new means to identify genetic components of vector competence (Nevoa et al 2018), monitor pathogen prevalence in vectors (Batovska et al 2018), and track genetic variation of pathogens (Miles et al 2017, Dumonteil et al 2018). Additionally, HTDS makes possible not only genetic tracking of pest outbreaks to identify outbreak origins (Dupuis et al 2018), but also allows us to identify, monitor, and predict insecticide resistance (Miles et al 2017, Clarkson et al 2018, Dada et al 2018).…”
Section: What New/emerging Technologies Have the Potential To Revolutmentioning
confidence: 99%